Report of chronic myeloid leukemia in chronic phase from Tata Memorial Hospital, Mumbai, 2002-2008 - Purvish Parikh (Indian Journal of Medical and Paediatric Oncology)
Background: Chronic myeloid leukemia (CML) is the commonest hematological malignancy in India. This manuscript is a single center analysis CML in chronic phase (CP). Materials and Methods: We did retrospective analysis of almost 1000 patients registered as chronic myeloid leukemia over a period of 6 years at Tata Memorial Hospital. Results: We found striking difference in cytogenetic response among patients presenting in late chronic phase (CP) compared with the patients in early CP. The rate of complete cytogenetic response among patients in late CP was 60% while in early CP it was 80%, which was statistically significant (P = 0.0001). The overall survival was 86%, at a median follow-up of 51 months. Innovator glivec was taken by 671 patients among which complete cytogenetic response (CCyR) was seen in 72% whereas generic veenat was taken by 237 patients and CCyR was seen in 75% of them. Conclusion: Availability of imatinib has dramatically changed the outlook for CML in India. The response was identical for those treated with innovator brand of imatinib as compared to the generic brand. Hence quality generics provide a cost effective solution, which is particularly relevant in the current global scenario.